Anti-swelling conductive gel material as well as preparation method and application thereof

By introducing hydrophobic fluorine-containing monomers and zirconium ions into the photocured 3D printed gel, a high crosslink density eutectic organic gel network structure is formed, which solves the problem of easy expansion of the gel under water, achieves good swelling resistance, mechanical properties and electrical conductivity, and expands its application range.

CN119529159APending Publication Date: 2025-02-28TAIYUAN UNIVERSITY OF TECHNOLOGY
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411710235.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The existing photocuring 3D printed gels are prone to expand underwater and humid environments, and their electrical conductivity and mechanical properties are insufficient, limiting their application range.

Method used

By introducing hydrophobic fluoroethyl acrylate (TFEA) and zirconium ions, a hydrophobic barrier and strong coordination bond are formed, and a eutectic solvent and crosslinking agent are combined to form a high crosslinking density eutectic organic gel network structure.

Benefits of technology

It realizes that the gel maintains good mechanical properties and conductivity when placed underwater for a long time, significantly improves swelling resistance and printability, and is suitable for flexible sensing, underwater communication and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119529159A_ABST
    Figure CN119529159A_ABST
Patent Text Reader

Abstract

The invention discloses an anti-swelling conductive gel material and a preparation method and application thereof, and belongs to the field of gel materials and 3D printing materials. The material is prepared from the following components in parts by mass: 55-65 parts of unsaturated polymer monomer; 35 to 45 parts of a solvent; 0.25 to 1 part of zirconium salt; 0.1 to 0.2 part of a cross-linking agent; 0.4 to 0.6 part of a photoinitiator; and 0.01 to 0.03 part of a light absorber. The preparation method solves the problem that the existing gel is easy to expand in a humid and underwater environment to cause deterioration of mechanical properties, and the gel material prepared by the method has good conductivity and mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an anti-swelling conductive gel material and a preparation method and application thereof, belonging to the technical field of gel materials and photocuring 3D printing. Background Art

[0002] In recent years, flexible electronic materials have developed rapidly and are widely used in various applications such as human motion detection, health monitoring, electronic skin, flexible sensors, and soft robots. As a kind of soft material, hydrogel contains a considerable amount of water, which promotes the transport of ions. It can also give the gel conductivity by introducing conductive ions, which can easily convert external stimuli into electrical signals. It also provides properties similar to human tissue and other organisms. These properties make hydrogel a popular choice for wearable and flexible electronic products.

[0003] However, the performance of hydrogels is closely related to their water content. Under dry or cold conditions, the water in the hydrogel will evaporate or freeze rapidly, causing its structure to shrink. Due to their high hydrophilicity, hydrogels often undergo inevitable swelling in aqueous environments. These conditions will cause irreversible damage to the structure and mechanical properties of hydrogels, severely limiting their scope of application. In addition, swelling will reduce the conductivity of hydrogels due to the dilution of the conductive network. To address these issues, hydrophobic ionic liquids have been explored to create a completely hydrophobic environment and provide waterproof properties for gel-type sensors. However, the use of ionic liquids (ILs) also has certain disadvantages, including high cost, complex synthesis process, and potential toxicity, which greatly hinder their practical application.

[0004] In addition to making the gel have satisfactory properties, advanced molding methods are also required. 3D printing is a rapidly developing manufacturing technology that has attracted widespread attention due to its flexibility and high precision. It can effectively produce flexible wearable devices and overcome the limitations of traditional mold manufacturing. At present, digital light processing (DLP) printing technology is popular due to its high efficiency and high precision. It can create complex structures with high resolution by realizing rapid photocuring through digital ultraviolet light projection. This molding method combined with gel materials will provide gel materials with broader application prospects. Therefore, based on photocuring 3D printing technology, designing a conductive gel material with anti-swelling properties has important research significance and application value. Summary of the invention

[0005] The present invention aims to provide an anti-swelling conductive gel material and a preparation method and application thereof, which solves the problem that the existing photocurable 3D printing gel is easy to swell underwater and in a humid environment, and the gel material has both good conductivity and mechanical properties.

[0006] The gel material provided by the present invention has good anti-swelling property, and the gel still has good mechanical properties and conductivity after being placed underwater for a long time. The present invention introduces the hydrophobic fluorinated monomer 2,2,2, trifluoroethyl acrylate (TFEA) into the polymer main chain, and the hydrophobic fluorinated side chain group acts as a diffusion barrier between the gel and the aqueous phase, giving the gel good anti-swelling property. Selecting a eutectic solvent as the solvent of the polymer network provides a wide temperature working window for the gel. The introduction of zirconium ions forms a strong coordination effect and gives the gel good conductivity at the same time. Various functional groups (such as ether and hydroxyl) in the gel produce numerous hydrogen bonds, coordination bonds and electrostatic interactions, which together provide physical crosslinking for the gel. Adding a crosslinking agent provides covalent crosslinking for the gel. The combination of the two crosslinkings gives the gel a high crosslinking density, further improving the anti-swelling property and mechanical properties of the gel. Under 405nm ultraviolet light irradiation, a eutectic organic gel network structure with strong coordination bonds is formed by free radical polymerization. This gel network exhibits excellent anti-swelling property, good mechanical properties and printability.

[0007] The invention provides an anti-swelling conductive gel material, which is prepared from the following components in parts by mass: 55-65 parts of unsaturated polymer monomers; 35-45 parts of solvents; 0.25-1 parts of zirconium salts; 0.1-0.2 parts of cross-linking agents; 0.4-0.6 parts of photoinitiators; and 0.01-0.03 parts of light absorbers.

[0008] The unsaturated polymer monomers include three types, the first of which is 2,2,2-trifluoroethyl acrylate, the second monomer is acrylic acid, and the third monomer is one of N-isopropylacrylamide, hydroxyethyl acrylate, hydroxyethyl methacrylate, and N-vinylpyrrolidone; the mass ratio of the first, second, and third unsaturated polymer monomers provided is 0.2~0.8:1:0.7.

[0009] The solvent is a eutectic solvent, which is composed of choline chloride and ethylene glycol; choline chloride is dissolved in ethylene glycol, heated and stirred until transparent to obtain the eutectic solvent, wherein the molar ratio of choline chloride to ethylene glycol is 1:3-3:1.

[0010] The zirconium salt is one of zirconium oxychloride and zirconium acetylacetonate.

[0011] The cross-linking agent is one of polyethylene glycol diacrylate and N,N'-methylenebisacrylamide.

[0012] The photoinitiator is one of phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide and diphenyl-(2,4,6-trimethylbenzoyl)phosphine oxide; the light absorber is one of Sudan Red I, Sudan Red IV and lemon yellow.

[0013] The present invention provides a method for preparing the above-mentioned anti-swelling conductive gel material, comprising the following steps: (1) First, three unsaturated polymer monomers are mixed, and then zirconium salt is added to the mixed unsaturated polymer monomers, and heated and stirred until uniformly dispersed to obtain a salt-containing monomer solution; the mass ratio of zirconium salt to unsaturated polymer monomer is 0.25~1:55~65; (2) mixing choline chloride and ethylene glycol, heating and stirring until transparent and clear, to obtain a eutectic solvent; the molar ratio of choline chloride to ethylene glycol is 1:3 to 3:1; (3) mixing the solutions obtained in step (1) and step (2), and stirring them fully at room temperature to obtain a gel solution; the mass ratio of the unsaturated polymer monomer to the eutectic solvent is 55-65:35-45; (4) adding a crosslinking agent, a photoinitiator and a light absorber to the solution prepared in step (3) in sequence, stirring at room temperature until the solution is uniform and free of precipitation, thereby obtaining a 3D printing gel ink; (5) Slicing the STL format three-dimensional model using software, pouring the gel ink prepared in step (4) into the material tank of the light-curing 3D printer for printing; (6) The gel printed in step (5) is ultrasonically cleaned with ethanol, and then cured for a second time in a curing box to obtain an anti-swelling conductive gel material.

[0014] In the above preparation method, the heating temperature in step (1) and step (2) is 40 to 70°C.

[0015] The stirring speed in steps (1) to (4) is 400 to 1000 r / min.

[0016] The slice layer thickness described in step (5) is 0.01 to 0.05 mm, and the single layer curing time is 10 to 30 seconds.

[0017] The ultrasonic cleaning time in step (6) is 5 to 10 minutes, and the secondary curing time is 10 to 30 minutes.

[0018] The present invention provides an application of the anti-swelling conductive gel material in the manufacture of soft materials, wherein the soft materials include flexible conductive materials, soft tissue preoperative models, hand-made models, and the like.

[0019] Beneficial effects of the present invention: (1) The photocurable 3D printing anti-swelling conductive gel material provided by the present invention introduces hydrophobic fluorinated monomers to form a hydrophobic barrier and zirconium ions to form strong coordination bonds, has excellent anti-swelling effect, and can be stably applied in the fields of flexible sensing, underwater communication, soft robots, and hand-made models.

[0020] (2) The anti-swelling conductive gel provided by the present invention has good compatibility with the light-curing 3D printers on the market and can be used in various DLP and LCD printers and customized according to needs.

[0021] (3) The photocurable 3D printed anti-swelling conductive gel provided by the present invention has adjustable mechanical properties, anti-swelling properties and conductive properties, so that it can be used in various scenarios. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 The figure shows the comparison of the swelling rates of the dumbbell-shaped gel prepared in Example 1 of the present invention after being exposed at room temperature for 7 days.

[0023] Figure 2 The mechanical diagrams of the dumbbell-shaped gel prepared in Example 1 of the present invention at the 1st, 100th, 200th, 300th, 400th and 500th cycles in 500 cycles in water and air respectively.

[0024] Figure 3 This is a comparison chart of the swelling rates of gels with different contents of hydrophobic monomers in Example 2 of the present invention after being placed underwater for 24 hours.

[0025] Figure 4 This is the stress-strain diagram of the gel with different contents of zirconium salt in Example 3 of the present invention.

[0026] Figure 5 This is a comparison chart of the swelling rates of gels with different zirconium salt contents in Example 3 of the present invention after being placed underwater for 24 hours.

[0027] Figure 6 This is a hollow structure sample printed by Example 4 of the present invention.

[0028] Figure 7 This is the school badge model printed by Example 5 of the present invention.

[0029] Figure 8 This is a schematic diagram of the school badge model printed according to Example 5 of the present invention after being placed underwater for 7 days.

[0030] Fig. 9 The electrical impedance diagrams obtained by bending the finger cuff printed in Example 5 of the present invention at different angles. DETAILED DESCRIPTION

[0031] The present invention is further illustrated by the following examples, but is not limited to the following examples.

[0032] Example 1: Comparison of a hydrogel material prepared by a conventional method and an anti-swelling conductive gel material prepared by the method of the present invention Preparation of DES solution: Choline chloride (ChCl) and ethylene glycol (EG) were mixed in a molar ratio of 1:2 and heated in a 60 °C water bath for 1 h to form a homogeneous colorless liquid as a deep eutectic solvent (DES).

[0033] Add 34 parts of acrylic acid, 23 parts of hydroxyethyl methacrylate, 0.2 parts of polyethylene glycol diacrylate and 0.5 parts of diphenyl-(2,4,6-trimethylbenzoyl)phosphine into beaker 1, stir and dissolve, then add 40 parts of deionized water into beaker 1 and stir for 30 min to obtain a hydrogel precursor solution; add 27 parts of acrylic acid, 18 parts of hydroxyethyl methacrylate and 15 parts of 2,2,2-trifluoroethyl acrylate into beaker 2, then add 1 part of ZrOCl2·8H2O, add a magnet and place in a water bath, stir at 60°C for 30 min until the solution is clear. Add 40 parts of DES solution to beaker 2 and stir at room temperature until the solution is clear; finally, add 0.2 parts of polyethylene glycol diacrylate and 0.5 parts of diphenyl-(2,4,6-trimethylbenzoyl)phosphine oxide, stir at room temperature in the dark until fully dissolved, and obtain a eutectic gel precursor solution; use a pipette to draw the above two gel precursor solutions into a dumbbell-shaped mold, irradiate under ultraviolet light for 300s, and obtain hydrogel and eutectic gel samples. The former is a hydrogel material prepared using water as a solvent, and the latter is a eutectic gel material prepared using a eutectic solvent.

[0034] In this example, two gels were prepared using two different solvents to evaluate the anti-swelling properties of the gels. The two gels were immersed in a beaker containing 100 ml of deionized water to compare their anti-swelling properties. The results are as follows: Figure 1 As shown in the left figure, after being immersed in water for 7 days, it can be directly observed that the volume of the eutectic gel prepared by the method of the present invention has no obvious change, and has a certain anti-swelling property, while the hydrogel of the comparative product has obvious swelling ( Figure 1 The upper part of the left figure shows the swelling effect of the hydrogel before and after 7 days, and the lower part shows the swelling effect of the eutectic gel before and after 7 days). Figure 1 As shown in the figure on the right, the volume of the hydrogel increases immediately after one day of immersion, and the weight reaches 1.2 times its original value. Although the volume mass of the eutectic gel has a slight increase in swelling rate within the first day, it decreases with the increase of immersion time and approaches zero. The final equilibrium swelling rate is only 1.79%, indicating that the eutectic gel has excellent anti-swelling properties.

[0035] Dumbbell-shaped specimens of the eutectic gel were subjected to 500 100% tensile cycle tests in water and air, respectively. Figure 2), showing that the dissipated energy of the gel remained almost unchanged from the 200th cycle to the 500th cycle, indicating that it has good fatigue resistance at 500% strain in both air and water. The eutectic gel exhibits a larger hysteresis loop and higher residual strain underwater than in air. This indicates that some water molecules are replaced into the gel to form hydrogen bonds, leading to the strengthening of the polymer network. This shows that this gel has good elasticity and tensile stability.

[0036] Example 2: Preparation of anti-swelling conductive gel material by changing the amount of 2,2,2-trifluoroethyl acrylate using the method of the present invention Take five beakers and record them as beaker 1, beaker 2, beaker 3, beaker 4 and beaker 5 respectively. Add 27 parts of acrylic acid and 18 parts of hydroxyethyl methacrylate to the four beakers respectively, and then add 0, 5, 10, 15 and 20 parts of 2,2,2-trifluoroethyl acrylate to each of them, stir for 30 min at room temperature until uniform dispersion, then add 40 parts of DES solution (prepared in the same way as in Example 1) and stir at room temperature until the solution is clear, finally add 0.2 parts of polyethylene glycol diacrylate and 0.5 parts of diphenyl-(2,4,6-trimethylbenzoyl)phosphine oxide, stir at room temperature in the dark until fully dissolved, and obtain eutectic gel precursor solution. Use a pipette to draw the above five gel precursor solutions into a mold with a diameter of 20 mm and a thickness of 2 mm, and irradiate them for 300 s under light with a wavelength of 405 nm to obtain five cylindrical gel samples with different contents of 2,2,2-trifluoroethyl acrylate.

[0037] This example tests the adjustability of the anti-swelling property of the gel material: five cylindrical gel samples with different contents of 2,2,2-trifluoroethyl acrylate are immersed in 100 ml of deionized water, and the weight of the eutectic gel after immersion for 24 hours is recorded. The anti-swelling test is then performed on the samples ( Figure 3 ). It was found that when 5 parts of 2,2,2-trifluoroethyl acrylate were added, the swelling rate of the eutectic gel was reduced by about 40% compared with the eutectic gel without 2,2,2-trifluoroethyl acrylate, which significantly improved the anti-swelling performance of the gel. When the mass fraction of 2,2,2-trifluoroethyl acrylate was 20 parts, the swelling rate of the gel increased slightly. This may be due to the fact that too much hydrophobic substance caused the polymer network structure to change, affecting the stability of the gel, making it easier for water molecules to penetrate, resulting in an increase in the swelling rate. This reflects the adjustability of the anti-swelling performance of this gel material, so that the performance of the gel can be adjusted according to needs.

[0038] Example 3: Preparation of anti-swelling conductive gel material by changing the amount of zirconium salt used by the method of the present invention Take four beakers and record them as beaker 1, beaker 2, beaker 3 and beaker 4 respectively. Add 27 parts of acrylic acid, 18 parts of hydroxyethyl methacrylate and 15 parts of 2,2,2-trifluoroethyl acrylate to the four beakers respectively, and then add 0.25, 0.5, 0.75 and 1 parts of ZrOCl2·8H2O respectively, stir in a water bath at 60°C for 30 min until uniform dispersion, then add 40 parts of DES solution (prepared by the method of Example 1) and stir at room temperature until the solution is clear, finally add 0.2 parts of polyethylene glycol diacrylate and 0.5 parts of diphenyl-(2,4,6-trimethylbenzoyl) phosphine oxide, stir at room temperature in the dark until fully dissolved, and obtain eutectic gel precursor solution. Use a pipette to draw the above four gel precursor solutions into dumbbell-shaped molds respectively, irradiate under light with a wavelength of 405nm for 300s, and obtain four dumbbell-shaped tensile parts with different zirconium salt contents.

[0039] This example tests the mechanical properties of the gel material and the adjustability of its anti-swelling property: stress-strain tests are performed on dumbbell-shaped tensile pieces with four different zirconium salts ( Figure 4 ) and anti-swelling test ( Figure 5 ), it was found that with the increase of zirconium salt content, the number of coordination bonds increased, the fracture strength of the gel increased significantly, and the strong coordination bonds further increased the crosslinking density of the eutectic gel, which gradually improved the anti-swelling property of the gel. This reflects the adjustability of the tensile strength and anti-swelling properties of this gel material, so that the performance of the gel can be adjusted according to needs. Example 4

[0040] Add 27 parts of acrylic acid, 18 parts of hydroxyethyl methacrylate and 10 parts of 2,2,2-trifluoroethyl acrylate to a beaker, then add 0.75 parts of ZrOCl2·8H2O, add a magnet and place in a water bath, stir at 60°C for 30 min until the solution is clear. Mix choline chloride (ChCl) and ethylene glycol (EG) in a molar ratio of 1:2 and heat in a 60°C water bath for 1 hour to form a uniform colorless liquid as a deep eutectic solvent (DES), then add 40 parts of DES solution and stir at room temperature until the solution is clear. Finally, add 0.2 parts of polyethylene glycol diacrylate, 0.5 parts of diphenyl-(2,4,6-trimethylbenzoyl) phosphine oxide and 0.03 parts of lemon yellow, stir at room temperature away from light until fully dissolved, and obtain a eutectic gel solution, which is printing ink, and store it for use; Printing of eutectic gel: Pour the prepared printing ink into the liquid tank of the DLP 3D printer and print according to the following printing parameters as required.

[0041]

[0042] This embodiment uses a DLP 3D printer to print complex structures with high precision. After printing, the model is taken out, ultrasonically cleaned in alcohol for 2 minutes, and then placed in a curing box for curing for 10 minutes to obtain the final required model sample.

[0043] This embodiment prints a relatively high-precision hollow structure. Figure 6 The printed hollow structure has structural details that are exactly the same as the original digital model. Example 5

[0044] Add 27 parts of acrylic acid, 18 parts of hydroxyethyl methacrylate and 15 parts of 2,2,2-trifluoroethyl acrylate to a beaker, then add 1 part of ZrOCl2·8H2O, add a magnet and place in a water bath, stir at 60°C for 30 min. Mix choline chloride (ChCl) and ethylene glycol (EG) in a molar ratio of 1:2 and heat in a 60°C water bath for 1 hour to form a uniform colorless liquid as a deep eutectic solvent (DES), then add 40 parts of DES solution and stir at room temperature until the solution is clear, finally add 0.2 parts of polyethylene glycol diacrylate and 0.5 parts of diphenyl-(2,4,6-trimethylbenzoyl) phosphine oxide and 0.01 parts of lemon yellow, stir at room temperature away from light until fully dissolved, and obtain a eutectic gel solution, which is printing ink, and store it for use;

[0045] This embodiment uses an LCD 3D printer to print complex structures with high precision. After printing, the model is taken out, ultrasonically cleaned in alcohol for 2 minutes, and then placed in a curing box for 10 minutes to obtain the final required model sample. The light intensity of the LCD 3D printing light source is weaker than that of the DLP 3D printing light source, the content of the added light absorber is relatively reduced, and the illumination time of each layer is relatively increased.

[0046] Figure 7 For printing school badge model, Figure 8 This is a schematic diagram of the gel after being placed underwater for 7 days. It can be seen that its outline and structural details are basically consistent with the original state, indicating that the printed eutectic gel has good anti-swelling properties. Fig. 9 It is an electrical sensing test performed on the finger wearing the printed finger sleeve. The bending angle of the finger can be distinguished by the detected signal curve, indicating that the gel has good conductivity and electrical stability.

Claims

1. An anti-swelling conductive gel material, characterized in that: It is prepared from the following components in parts by weight: Unsaturated polymer monomer: 55~65 parts; Solvent: 35~45 parts; Zirconium salt: 0.25~1 part; Cross-linking agent: 0.1~0.2 parts; Photoinitiator: 0.4~0.6 parts; Light absorber: 0.01~0.03 parts.

2. The anti-swelling conductive gel material according to claim 1, characterized in that: The unsaturated polymer monomers include three types, the first of which is 2,2,2-trifluoroethyl acrylate, the second monomer is acrylic acid, and the third monomer is one of N-isopropylacrylamide, hydroxyethyl acrylate, and hydroxyethyl methacrylate; the mass ratio of the first, second, and third unsaturated polymer monomers provided is 0.2~0.8:1:0.

7.

3. The anti-swelling conductive gel material according to claim 1, characterized in that: The solvent is a eutectic solvent, which is composed of choline chloride and ethylene glycol; choline chloride is dissolved in ethylene glycol, heated and stirred until transparent to obtain the eutectic solvent, wherein the molar ratio of choline chloride to ethylene glycol is 1:3-3:

1.

4. The anti-swelling conductive gel material according to claim 1, characterized in that: The zirconium salt is one of zirconium oxychloride and zirconium acetylacetonate.

5. The anti-swelling conductive gel material according to claim 1, characterized in that: The cross-linking agent is one of polyethylene glycol diacrylate and N,N'-methylenebisacrylamide.

6. The anti-swelling conductive gel material according to claim 1, characterized in that: The photoinitiator is one of phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide and diphenyl-(2,4,6-trimethylbenzoyl)phosphine oxide; the light absorber is one of Sudan Red I, Sudan Red IV and lemon yellow.

7. A method for preparing the anti-swelling conductive gel material according to any one of claims 1 to 6, characterized in that The following steps are involved: (1) First, three unsaturated polymer monomers are mixed, and then zirconium salt is added to the mixed unsaturated polymer monomers, and heated and stirred until uniformly dispersed to obtain a salt-containing monomer solution; the mass ratio of zirconium salt to unsaturated polymer monomer is 0.25~1:55~65; (2) dissolving choline chloride in ethylene glycol, heating and stirring until transparent and clear, to obtain a eutectic solvent; the molar ratio of choline chloride to ethylene glycol is 1:3 to 3:1; (3) mixing the solutions obtained in step (1) and step (2), and stirring them uniformly at room temperature to obtain a gel solution; the mass ratio of the unsaturated polymer monomer to the eutectic solvent is 55-65:35-45; (4) adding a crosslinking agent, a photoinitiator and a light absorber to the solution prepared in step (3) in sequence, stirring at room temperature until the solution is uniform and free of precipitation, thereby obtaining a 3D printing gel ink; (5) Slicing the STL format three-dimensional model using software, pouring the gel ink prepared in step (4) into the material tank of the light-curing 3D printer for printing; (6) The gel printed in step (5) is ultrasonically cleaned with ethanol, and then cured for a second time in a curing box to obtain an anti-swelling conductive gel material.

8. The method for preparing the anti-swelling conductive gel material according to claim 7, characterized in that: The heating temperature in step (1) and step (2) is 40 to 70° C.; the stirring speed in steps (1) to (4) is 400 to 1000 r / min.

9. The method for preparing the anti-swelling conductive gel material according to claim 7, characterized in that: The slice layer thickness described in step (5) is 0.01-0.05 mm, and the single layer curing time is 10-30 s; the ultrasonic cleaning time described in step (6) is 5-10 min, and the secondary curing time is 10-30 min.

10. Use of the anti-swelling conductive gel material according to any one of claims 1 to 6 in the manufacture of soft materials, wherein the soft material comprises a flexible conductive material, a soft tissue preoperative model or a hand-made model.

Citation Information

Patent Citations

  • High-tensile conductive hydrogel for photo-curing 3D printing and preparation method thereof

    CN111423536A

  • Conductive hydrogel as well as preparation method and application thereof

    CN114671963A

  • Application of high-strength hydrogel as printing ink in photocuring 3D printing

    CN114958079A

  • Preparation method and application of photocuring 3D printing hydrogel metamaterial

    CN116041884A

  • Dual-network deep eutectic gel as well as preparation method and application thereof

    CN118027452A